Mineral Phases and Release Behaviors of As in the Process of Sintering Residues Containing As at High Temperature - Xingrun Wang; Fengsong Zhang; Zexi Nong (The Scientific World Journal)
To investigate the effect of sintering temperature and sintering time on arsenic volatility and arsenic leaching in the sinter, we carried out experimental works and studied the structural changes of mineral phases and microstructure observation of the sinter at different sintering temperatures. Raw materials were shaped under the pressure of 10 MPa and sintered at 1000~1350°C for 45 min with air flow rate of 2000 mL/min. The results showed that different sintering temperatures and different sintering times had little impact on the volatilization of arsenic, and the arsenic fixed rate remained above 90%; however, both factors greatly influenced the leaching concentration of arsenic. Considering the product’s environmental safety, the best sintering temperature was 1200°C and the best sintering time was 45 min. When sintering temperature was lower than 1000°C, FeAsS was oxidized into calcium, aluminum, and iron arsenide, mainly Ca3(AsO4)2 and AlAsO4, and the arsenic leaching was high. When it increased to 1200°C, arsenic was surrounded by a glass matrix and became chemically bonded inside the matrix, which lead to significantly lower arsenic leaching.